Key Factors for Template‐Oriented Porous Titania Synthesis: Solvents and Catalysts. Issue 3 (15th January 2020) - Yin, Shanshan; Song, Lin; Xia, Senlin; Cheng, Yajun; Hohn, Nuri; Chen, Wei; Wang, Kun; Cao, Wei; Hou, Shujin; Müller‐Buschbaum, Peter
Abstract: Various types of titania nanostructures are synthesized with a polymer‐templated sol–gel method based on the amphiphilic diblock copolymer polystyrene‐b‐polyethylene oxide (PS‐b‐PEO) in combination with selective incorporation of the titania precursor titanium tetraisopropoxide. Custom tailoring of different types of titania morphologies is realized by changing the phase separation behavior of the PS‐b‐PEO template. Particularly, application of solvents from different categories is found to have a major impact upon the phase separation behavior of PS‐b‐PEO and the final titania film morphology. The amount of available hydrochloric acid catalyst during the gelation process is seen as an additional key factor to induce controllable morphological changes. Scanning electron microscopy and grazing incidence small angle X‐ray scattering measurements are carried out to study the surface and inner structure of porous titania films. Systematic analysis and comparison of different characterization results allow attributing the following three factors to the respectively formed titania nanostructure: the surface energy between PS blocks and surrounding solvent, the aggregation behavior of the titania nanoparticles, and the block‐specific selectivity of the used solvent. For all synthesized titania thin films, an anatase‐type crystallization is confirmed through X‐ray powder diffraction. Abstract : Application of solvents from different categories is demonstrated to have a major impact on the amphiphilic diblock copolymer polystyrene‐b‐polyethyleneoxide assisted sol–gel synthesis of nanostructured titania films.